REVIEW JURNAL : DIAGRAM, TABEL, DAN GRAFIK DALAM PENYAJIAN DATA - Fadli Tumanggor; Murni Ati; Almira Amir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Data presentation is a crucial part of scientific writing because it plays a role in conveying information clearly, systematically, and easily understood. Diagrams, tables, and graphs are the most commonly used forms of data presentation, yet inaccuracies in their selection are still common. This article aims to examine the concepts, functions, and advantages and limitations of using diagrams, tables, and graphs in data presentation. The method used is a literature study with a descriptive qualitative approach through a review of national and international scientific journals, research methodology books, and other relevant scientific sources. The results of the study indicate that tables are more effective for presenting data in a detailed and structured manner, while diagrams and graphs emphasize visual aspects, making it easier for readers to quickly understand patterns, comparisons, and trends in the data. The selection of the appropriate form of data presentation must be tailored to the type of data, the purpose of the presentation, and the characteristics of the reader to avoid misinterpretation of the information. Therefore, a good understanding of the use of diagrams, tables, and graphs is crucial for improving the quality of data presentation in research and scientific papers, particularly in the field of education.